A mobile interface for navigating hierarchical information space. (December 2015) - Chhetri, Abhishek P.; Zhang, Kang; Jain, Eakta
Abstract: This paper presents ERELT (Enhanced Radial Edgeless Tree), a tree visualization approach on modern mobile devices. ERELT is designed to offer a clear visualization of any tree structure with intuitive interaction. Such visualization can assist users in interacting with a hierarchical structure such as a media collection, file system, etc. In the ERELT visualization, a subset of the tree is displayed at a time. The displayed tree size depends on the maximum number of tree elements that can be put on the screen while maintaining clarity. Users can quickly navigate to the hidden parts of the tree through touch-based gestures. We have conducted a user study to evaluate this visualization for a music collection. The study results show that this approach reduces the time and effort in navigating tree structures for exploration and search tasks. Highlights: We implemented a tree visualization as a UI for hierarchical structures for phones. We compared our UI against traditional list layout found in modern smartphones. We displayed media library in a music app as tree and list UI for user tests. The tree UI requires lesser number of touches than list UI for most of the tasks. The tree UI takes lesser time for exploration and search in hierarchical structure.